2020
DOI: 10.1002/rse2.139
|View full text |Cite
|
Sign up to set email alerts
|

Combining optical and radar satellite image time series to map natural vegetation: savannas as an example

Abstract: Up-to-date land cover maps are important for biodiversity monitoring as they are central to habitat and ecosystem distribution assessments. Satellite remote sensing is a key technology for generating these maps. Until recently, land cover mapping has been limited to static approaches, which have primarily led to the production of either global maps at coarse spatial resolutions or geographically restricted maps at high spatial resolutions. The recent availability of optical (Sentinel-2) and radar (Sentinel-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
0
25
0
2
Order By: Relevance
“…A total of 39 EO data types were used in the reviewed studies. This reflects a wide range of EO applications for savanna mixed pixel analysis [47,105,[113][114][115][116][117][118]. Of these, 26 (89%) were optical, 11 (7%) radar, 2 (3%) LiDAR, and 1 (1%) were a combination of optical hyperspectral and LiDAR.…”
Section: Type Of Earth Observation Data Usedmentioning
confidence: 89%
See 2 more Smart Citations
“…A total of 39 EO data types were used in the reviewed studies. This reflects a wide range of EO applications for savanna mixed pixel analysis [47,105,[113][114][115][116][117][118]. Of these, 26 (89%) were optical, 11 (7%) radar, 2 (3%) LiDAR, and 1 (1%) were a combination of optical hyperspectral and LiDAR.…”
Section: Type Of Earth Observation Data Usedmentioning
confidence: 89%
“…Borges et al [123] used Sentinel-1 and Sentinel-2 to map savanna land cover, and Naidoo et al [83] tested the utility of multi-seasonal and multi-sensor use of Landsat TM/ETM and ALOS PALSAR to map woody fractional cover over South Africa's semi-arid savannas. All three studies reported higher and improved accuracies for models which integrated SAR with optical data [109,113].…”
Section: Type Of Earth Observation Data Usedmentioning
confidence: 94%
See 1 more Smart Citation
“…Sentinel-2 memiliki 13-band spektral yaitu band 2,3,4 dan 8 dengan ketelitian spasial 10 m, band 5,6,7, 8a, 11 dan 12 mempunyai ketelitian spasial 20 m dan band 1, 9, dan 10 memiliki ketelitian spasial 60 m (Esa, 2013). Citra sentinel-2 banyak digunakan untuk identifikasi dan analisis permasalahan terkait dengan lingkungan, perencanaan perkotaan, deteksi perubahan tutupan lahan, pemetaan resiko bencana dan beragam aplikasi lainnya (Clerici, Valbuena Calderón & Posada, 2017;Tavares et al, 2019;Lopes et al, 2020).…”
Section: Pendahuluanunclassified
“…In recent connectivity studies, satellite remote sensing is becoming increasingly common to map land cover (Bergl et al, 2012;Bleyhl et al, 2017;Osipova et al, 2018Osipova et al, , 2019a. Satellite imagery, and particularly Sentinel-1 and 2 imagery from the ESA Copernicus programme, has great potential to produce accurate land cover classifications (Lopes et al, 2020;Mercier et al, 2019). Besides being open access, Sentinel data offers high spatial resolution and a high revisit time.…”
Section: Introductionmentioning
confidence: 99%